Irony in Matt Bettinelli Olpin And Tyler Gillet's Abigail (2024) - Yulianti, Sinta Augina; Sudarisman, Yoga; Fauzi, Erfan Muhamad (Universitas Muhammadiyah Gresik, 2025)
This research contributes to the analysis of irony that builds the horror formula. Irony is one of the techniques used in movies to convey the message of the contradiction between hope and reality. The movie Abigail (2024) by Matt Bettinelli Olpin and Tyler Gillet illustrates that irony can construct a horror formula. The analysis in this study aims to find out what aspects of irony are contained in Matt Bettinelli Olpin and Tyler Gillet's Abigail (2024) and to identify aspects of irony that construct the horror formula in Matt Bettinelli Olpin and Tyler Gillet's Abigail (2024). This research uses Petrie and Boggss' theory for irony, while the horror formula theory used is Sarricks' theory. This research uses a descriptive qualitative analysis method to analyze the data. The results of the study found six types of irony that help construct the horror formula: dramatic irony, irony of situation, irony of character, irony of setting, irony of tone, and cosmic irony. The data used are dialog scenes collected in the form of screenshots.